The Situation of Hungarian Farmers in the Age of 3.0 and 4.0 Agriculture: Agricultural Deprivation and Social Innovations - Bazsik, István; Bujdoso, Zoltan; Koncz, Gabor (Acta Carolus Robertus, 2022)
Agriculture is undergoing a revolution. The explosive technological development of industry is such that it can be considered the 4th industrial revolution. This process has spilled over into the agriculture and we are now talking about Agriculture 4.0 too, driven by innovation based on information technology throughout the agricultural sector. In the case of agriculture, for a number of reasons, it is inevitable to increase production efficiency, which can be achieved through R&D&I, i.e. research, development and innovation. The exponentially developing technology has many positive results, as it increases production efficiency and volume, improves quality, allows for higher levels of automation and real-time optimisation. However, there are also risks. Among these threats, this paper will focus on the problems facing domestic farmers and the principles of how to overcome them. Agricultural farmers in less developed countries, including Hungary, are unable to integrate the technological innovations produced by Agriculture 4.0 into their own economies at the appropriate pace and to use them effectively, as even the majority of farmers have not yet been able to adopt the achievements of Agriculture 3.0, and their effective access to modern technology is therefore increasingly doubtful. In Hungary, small and medium-sized enterprises in the agricultural sector are particularly vulnerable to being deprived of modern technologies for both subjective and objective reasons. This situation is either not being resolved or is extremely difficult to resolve. The term ’agricultural deprivation’ is the most accurate way of describing the situation, since deprivation is permanent, it is very difficult to break out of it, and the gap with developed economies is widening even if the technological level of the deprived enterprise stagnates, but unfortunately it is more likely to worsen as the tools become obsolete, thus increasing deprivation, i.e. the technological development gap and the obsolescence of the farm’s tools.